PERANAN BANK PEMBANGUNAN DAERAH (BPD) SULTRA CABANG UNAAHA DALAM PENGEMBANGAN UKM SEKTOR JASA DI KABUPATEN KONAWE - Liswatin Liswatin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
The research objectives to be achieved in this research is to know the role of regional development bank (BPD) SULTRA branch unaaha in providing credit to the community for the development of service sector smes in konawe discrit. The sample in this study is the small and medium business actors in subdistrict unaaha which amounted to 23 people, from the result of the analysis obtained that the credit BPD Sultra branch unaaha have a real role in business development, especially smes service sector in the region unaaha. This is avidenced by the presence of loans borrowed able to increase their business. Keywords: the role of banks, UKM, small entrepreneurs.